2003
DOI: 10.1074/jbc.m210785200
|View full text |Cite
|
Sign up to set email alerts
|

An NS3 Serine Protease Inhibitor Abrogates Replication of Subgenomic Hepatitis C Virus RNA

Abstract: The hepatitis C virus (HCV) NS3 protease is essential for polyprotein maturation and viral propagation, and it has been proposed as a suitable target for antiviral drug discovery. An N-terminal hexapeptide cleavage product of a dodecapeptide substrate identified as a weak competitive inhibitor of the NS3 protease activity was optimized to a potent and highly specific inhibitor of the enzyme. The effect of this potent NS3 protease inhibitor was evaluated on replication of subgenomic HCV RNA and compared with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
61
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 47 publications
(41 reference statements)
7
61
0
Order By: Relevance
“…This is further proof of the high specificity of the inhibition. Earlier studies demonstrated that compound A inhibits proteolytic activity of NS3 in genotype 1b HCV (51). Our data show that compound A is also efficient in inhibiting genotype 1a NS3.…”
Section: Sds-page Analyses Of [supporting
confidence: 68%
See 1 more Smart Citation
“…This is further proof of the high specificity of the inhibition. Earlier studies demonstrated that compound A inhibits proteolytic activity of NS3 in genotype 1b HCV (51). Our data show that compound A is also efficient in inhibiting genotype 1a NS3.…”
Section: Sds-page Analyses Of [supporting
confidence: 68%
“…The NS3 protease is competitively inhibited by specific penta-or hexapeptides derived from the aminoterminal NS3 cleavage products (69,79). One potent and highly specific inhibitor of the NS3 protease activity (compound A) was shown to reduce replication of a subgenomic serotype 1b HCV RNA to undetectable levels in Huh7 cells (51).…”
Section: Sds-page Analyses Of [mentioning
confidence: 99%
“…HCV is an RNA virus and, in many cases, is difficult to eradicate from infected individuals even with an intensive antiviral therapy that utilizes IFN and ribavirin (7,14,15,25,30,41). Although a number of other antiviral compounds, including inhibitors against the NS3 protease and the RNA-dependent RNA polymerase of NS5B (1,4,8,39), are currently being tested for their therapeutic applicability, such attempts have not always been promising.…”
Section: Discussionmentioning
confidence: 99%
“…Whole-cell extracts obtained by lysing cells in Laemmli buffer were resolved by sodium dodecyl sulfate-8% polyacrylamide gel electrophoresis, transferred to a nitrocellulose membrane, and then blocked in 5% nonfat milk in Tris-buffered saline-Tween buffer. Blots were incubated with either E1A monoclonal antibody (NeoMarkers), ␣-fetoprotein (AFP) polyclonal antibody (NeoMarkers), albumin polyclonal antibody (Sigma), NS3 polyclonal antibody (27), or NS5A monoclonal antibody (Maine Biotech Services). Membranes were then incubated with the appropriate mouse-or rabbit-specific antibodies conjugated with horseradish peroxidase, developed by use of LumiLight Western blotting solution (Roche), and exposed to film (Hyperfilm; Amersham Pharmacia Biotech).…”
Section: Cell Culture and Generation Of Neomycin-and Zeocin-resistantmentioning
confidence: 99%
“…Approximately 10 5 cells were grown on LabTek 4-well chamber slides (Nalge Nunc International) that were precoated with 150 g of poly-D-lysine per ml. At 1 day postseeding, cells were fixed with 4% paraformaldehyde, permeabilized with 0.2% Triton X-100, and then incubated with either a polyclonal antibody against NS3 protein (27) or a monoclonal antibody against NS5A (Maine Biotech Services), and bound antibodies were detected with AlexaFluor 488 goat-anti-rabbit or AlexaFluor 488 goat anti-mouse antibody, respectively (Molecular Probes). Cells were visualized with a fluorescence detection microscope (Olympus).…”
Section: Cell Culture and Generation Of Neomycin-and Zeocin-resistantmentioning
confidence: 99%